Science and the Afterlife Experience: Evidence for the Immortality of Consciousness by Chris Carter - Matlock, James G. (Journal of Scientific Exploration, 2014)
Science and the Afterlife Experience is the concluding volume of a trilogy that began with Parapsychology and the Skeptics (Carter 2007; reissued as Science and Psychic Phenomena, Carter 2012) and continued with Science and the Near-Death Experience (Carter 2010). These books provide handy introductions to parapsychology, psychical research, and allied concerns (such as the near-death experience) for a new generation of readers. They may best be described as quasi-scholarly, aimed primarily at a general (non-academic) audience, although they include notes, reference lists, and indexes. Carter, who holds an M.A. from the University of Oxford, England, identifies himself as a philosopher and here and there addresses philosophical concerns, such as the implications of “paranormal” phenomena for concepts of personal identity. One of the hallmarks of the series is the attention given to materialistic skeptical positions, extended in the volume under review to include super-ESP.